2017
DOI: 10.1016/j.yexmp.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, microbiome, life style influence alcohol and non-alcoholic organ damage

Abstract: This paper is based upon the "8th Charles Lieber's Satellite Symposium" organized by Manuela G. Neuman at the Research Society on Alcoholism Annual Meeting, on June 25, 2016 at New Orleans, Louisiana, USA. The integrative symposium investigated different aspects of alcohol-induced liver disease (ALD) as well as non-alcohol-induced liver disease (NAFLD) and possible repair. We revealed the basic aspects of alcohol metabolism that may be responsible for the development of liver disease as well as the factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 242 publications
(262 reference statements)
1
50
0
Order By: Relevance
“…Indeed, ethanol has been shown to have many effects on the liver. It reaches the liver via the portal vein, induces triglyceride accumulation and hepatic oxidative stress in the liver, and also increases gut permeability . Zhu et al demonstrated that patients with NASH exhibit significantly elevated blood ethanol levels compared to those without NASH .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ethanol has been shown to have many effects on the liver. It reaches the liver via the portal vein, induces triglyceride accumulation and hepatic oxidative stress in the liver, and also increases gut permeability . Zhu et al demonstrated that patients with NASH exhibit significantly elevated blood ethanol levels compared to those without NASH .…”
Section: Discussionmentioning
confidence: 99%
“…Through the portal vein that connects the liver to the gastrointestinal tract, the liver is exposed to the influence of the gut microbiome. Perturbations of the gut microbiome, coupled with disturbances in gut barrier function, have been associated with common liver disorders, such as non-alcoholic fatty liver disease [138][139][140], non-alcoholic steatohepatitis [139,[141][142][143][144][145][146][147][148][149][150][151][152], alcoholic liver disease [139,140,142,145,147,148,150,151,[153][154][155][156][157][158][159][160][161][162][163][164], and liver cirrhosis [165][166][167][168][169][170]. Thus, the microbiome serves as a modulator of liver rhythmic functions.…”
Section: Liver Functionmentioning
confidence: 99%
“…(32,33) Additionally, ethanol reaches the liver through the portal vein, inducing triglyceride accumulation and hepatic oxidative stress, and increasing gut permeability. (34) Previous epidemiological studies have suggested a synergistic effect of alcohol and obesity on liver disease morbidity and mortality. (18,19) In our study, there were significant interactions between obesity and alcohol intake categories for incident HS, and between obesity and alcohol intake categories for incident HS plus an intermediate/high probability of advanced fibrosis.…”
Section: Discussionmentioning
confidence: 99%